A new spider species of the Pholcus yichengicus species group (Araneae, Pholcidae) from Hebei Province, northern China - Jinglin Li; Xiaoqing Zhang; Zhiyuan Yao (Biodiversity Data Journal)
The Pholcus yichengicus species group currently contains 47 species. It is mainly distributed in central and southern China, as well as northern Thailand.Pholcus changli Yao, sp. nov. is described as a new species of the P. yichengicus species group collected from northern China (Hebei Province).